Analisis Penerapan Halal Supply Chain Management dalam Meningkatkan Kepercayaan Konsumen UMKM Al-Izza - Hidayat, Nurul; Komang Kathy Saputri, Noer Ayu; Qurratu A'yunii, Khammada (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This article aims to analyze the application of Halal Supply Chain Management in increasing consumer confidence in UMKM Al-Izza products.The research method carried out is descriptive research with a qualitative approach. Data was collected through interviews with UMKM owners and consumers, as well as direct observation at production sites. This study concludes The implementation of halal supply chain management in UMKM Al-Izza includes a series of activities involving the provision of materials, including the stage of direct purchase of goods and storage of goods. The next step includes production activities that involve taking materials from storage warehouses, product production processes, and continued with distribution activities that include delivering products to sales locations and sales processes. Islamic consumers who consume UMKM Al-Izza products argue that halal products are very important, especially for Muslims, related to the belief that the products sold by UMKM Al-Izza are halal products because of clean sales places, clean safe production sites avoid haram substances, neat packaging and there are halal compositions and logos, and the ingredients used, and also Muslim-majority neighborhoods